COMPARATIVE ANALYSIS BETWEEN SKINFOLD THICKNESS AND BIOELETRIC IMPEDANCE FOR BODY FAT PERCENT MEASUREMENTS IN SOCCER PLAYERS (Fiep Bulletin - online, 2013)
The estimate of body fat percentage (BF%) by bioelectrical impedance (BIA) and skinfold thickness (ST) has the advantage of simplicity of measurement. However, the reliability of both methods still have been criticized. The aim of this study was to make a comparative analysis between the methods for estimating the BF% through the techniques of bioelectrical impedance and skinfold thickness (ST). The sample consisted of 22 soccer players in the junior category of a professional soccer team, homogenized by gender (male) and age (18 and 20 years). For determination of BF% by bioelectrical impedance Tetrapolar was used the apparatus Maltron trend, model 906 and the electronic scale Bipolar Tanita model UM-80. For ST we used the equation ? 4 ST (PETROSKI, 1995) then the equations of Siri (1961). After analyzing the data it was found that the BF% obtained by BIA Tetrapolar was 10.2±1.4%, 11.5±2.8% by bipolar and 11.2±2,3% by skinfold thickness. BIA measures did not differ significantly from each other (p = 0.0660), nor for BF% estimated by the ST (and ST Tetrapolar, p = 0.1048, and Bipolar ST, p = 0.7004). Despite the results, there is no data to indicate a device rather than others. The results of the BIA were similar as to the estimate of BF%.
Keywords: Body fat; bioeletric impedance; skinfolds thickness